Guest Editorial: Education for Information - Raghavan, K.S. (DESIDOC Journal of Library & Information Technology, 2002)
A US Education Department paper issued in 1988 stated: "The world of tomorrow which would usher in an information rich and technology intensive society, calls for new approaches to learning", These words reflect the challenge ahead for educational planners in every branch of knowledge including information.science.The subject of education for information has been the focus of many seminars, workshops and conferences in recent times. Agreement on what is good, necessary and feasible in India is not easy. This is no different from anywhere else in the world.However, before discussing the subject it is necessary to be on firm grounds; to be sure of what we are talking about. Therefore, definitions must come quite early in any discussion on the subject. http://dx.doi.org/10.14429/dbit.15.6.3207